A case of severe DRESS syndrome treated with therapeutic plasma exchange and intravenous immunoglobulin therapy. Issue 6 (15th July 2022) - Durak, Cansu; Aydemir, Sezin; Varol, Fatih; Aygün, Fatih; Çokuğraş, Haluk Cezmi
Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome in children is a rare adverse drug reaction with skin rash, fever, hematologic abnormalities, and multiorgan involvement. The diagnosis is difficult because of its various clinical presentations, nonetheless is extremely important due to the mortality rate. We describe a 14‐year‐old boy who developed hypersensitivity to either teicoplanin or meropenem therapy. After failing to improve with corticosteroids, he was successfully treated with therapeutic plasma exchange (TPE). TPE should be considered in the treatment with corticosteroid‐resistant DRESS syndrome.